Cumplimiento de las medidas de protección expedidas por el juzgado mixto de requena en los procesos de violencia familiar – 2021 - Vargas Paima, Tatiana (2024)
Requena is not alien to the administration of justice by the person who exercises such a monopoly, the Judicial Power, in this function the Mixed Court of Requena is the one who exercises, since there is no Family Court as provided by Law No. 30364, the function of granting measures protection through the issuance of resolutions when aware of criminal acts in which the victims are women or members of the family group. The justification is theoretical and practical, the objectives are to determine if the protection measures issued by the Mixed Court of Requena in the special family violence processes in 2021 were effective, and specifically to know if the Mixed Court of Requena has issued within the deadline of law the protection measures in the special family violence processes in the year 2021, and establish whether the Mixed Court of Requena has carried out supervision of the protection measures issued in the special family violence processes in the year 2021. The type of investigation is basic, qualitative approach, non-experimental, descriptive and correlational design, the subject of the study is one hundred and twelve files on Special Processes of Family Violence issued by the Mixed Court of Requena analyzed using the data collection technique of documentary analysis. It was found that in the province of Requena the protection measures granted in 2021 were not effective because they were not issued within the respective period and because supervision of them was not carried out.